Leading schools during crisis what school administrators must know - Pepper, Matthew J. 1977- (IG library, 2010)
School leadership is synonymous with challenge. However, some school leaders face true crises - situations threatening the continuing existence of their school. Leading Schools During Crisis analyzes leadership and behaviors of principals in these extraordinary circumstances. A simultaneously scholarly and practice-oriented book, Leading Schools During Crisis proposes the first school-specific model of defining and analyzing crises. Through authentic case studies, Leading Schools During Crisis offers a detailed theoretical and practical analysis of each crisis and the lessons from it for all school leaders.